Immune response to third SARS‐CoV‐2 vaccination in seronegative kidney transplant recipients: Possible improvement by mycophenolate mofetil reduction. Issue 11 (12th September 2022) - Kantauskaite, Marta; Müller, Lisa; Hillebrandt, Jonas; Lamberti, Joshua; Fischer, Svenja; Kolb, Thilo; Ivens, Katrin; Koch, Michael; Andree, Marcel; Lübke, Nadine; Schmitz, Michael; Luedde, Tom; et al.
Abstract: Modification of vaccination strategies is necessary to improve the immune response to SARS‐CoV‐2 vaccination in kidney transplant recipients (KTRs). This multicenter observational study analyzed the effects of the third SARS‐CoV‐2 vaccination in previously seronegative KTRs with the focus on temporary mycophenolate mofetil (MMF) dose reduction within propensity matched KTRs. 56 out of 174 (32%) previously seronegative KTRs became seropositive after the third vaccination with only three KTRs developing neutralizing antibodies against the omicron variant. Multivariate logistic regression revealed that initial antibody levels, graft function, time after transplantation and MMF trough levels had an influence on seroconversion ( P < .05). After controlling for confounders, the effect of MMF dose reduction before the third vaccination was calculated using propensity score matching. KTRs with a dose reduction of ≥33% showed a significant decrease in MMF trough levels to 1.8 (1.2–2.5) μg/ml and were more likely to seroconvert than matched controls ( P = .02). Therefore, a MMF dose reduction of 33% or more before vaccination is a promising approach to improve success of SARS‐CoV‐2 vaccination in KTRs.